Trzech panow w lodce nie liczac psa - Jerome, Jerome K. (Jerome Klapka), 1859-1927.; Jerome, Jerome K. (Jerome Klapka), 1859-1927. (Warszawa : Mlodziezowa Agencja Wydawnicza, 1986)
A fictional account of three friends who boat down the Thames from Oxford to London. They recount the love and history of the villages they pass through.
Translation of: Three men in a boat.
Keywords: Thames River (England) -- Fiction